Management of Primary Sclerosing Cholangitis: Conventions and Controversies - Natasha Chandok; Gideon M Hirschfield (Canadian Journal of Gastroenterology)
Primary sclerosing cholangitis (PSC) is a chronic inflammatory cholangiopathy that results in fibrotic strictures and dilations of the intra- and extrahepatic bile ducts. PSC is uncommon, occurs predominantly in males and has a strong association with inflammatory bowel disease. While the pathogenesis of PSC has not been fully elucidated, emerging evidence supports roles for the innate and adaptive immune systems, and genome-wide analyses have identified several genetic associations. Using the best available evidence, the present review summarizes the current understanding of the diagnosis, pathogenesis and management of PSC. Despite its rarity, there is an urgent need for collaborative research efforts to advance therapeutic options for PSC beyond liver transplantation.